1994
DOI: 10.1083/jcb.126.6.1393
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotide dissociation inhibitor is essential for Rab1 function in budding from the endoplasmic reticulum and transport through the Golgi stack.

Abstract: Abstract. The small GTPase Rabl is required for vesicular traffic from the ER to the cis-Golgi compartment, and for transport between the cis and medial compartments of the Golgi stack. In the present study, we examine the role of guanine nucleotide dissociation inhibitor (GDI) in regulating the function of Rabl in the transport of vesicular stomatitis virus glycoprotein (VSV-G) in vitro. Incubation in the presence of excess GDI rapidly (h/2 < 30 s) extracted Rabl from membranes, inhibiting vesicle budding fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
2

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 76 publications
(197 reference statements)
12
70
2
Order By: Relevance
“…Excess GDI has been shown to block both ER-toGolgi and intra-Golgi transport events in vitro (Elazar et al, 1994;Peter et al, 1994). Our finding that excess GDI had relatively little effect on these transport steps in vivo is not necessarily contradictory.…”
Section: Rab11 As a Select Target Of Gdi In Vivocontrasting
confidence: 36%
See 1 more Smart Citation
“…Excess GDI has been shown to block both ER-toGolgi and intra-Golgi transport events in vitro (Elazar et al, 1994;Peter et al, 1994). Our finding that excess GDI had relatively little effect on these transport steps in vivo is not necessarily contradictory.…”
Section: Rab11 As a Select Target Of Gdi In Vivocontrasting
confidence: 36%
“…Overexpression of GDI can be used to alter the membrane association of rab proteins and thereby affect their function. Excess GDI added in vitro has been demonstrated to release GDP-bound rab proteins from membranes by forming a soluble complex (DiracSvejstrup et al, 1994;Peter et al, 1994;Ullrich et al, 1994). Excess GDI causes a marked inhibition in membrane transport most likely because rebinding of rab proteins to membranes is extremely inefficient under these conditions.…”
Section: Rab11 Is Selectively Released From Membranes By Overexpressementioning
confidence: 99%
“…Previous studies have established that the Rab1 GTPase functions as a molecular switch in the ER 3 Golgi transport pathway (89,90). Introduction of the amino acid substitution, N121I, into Rab1B drastically reduces its affinity for GTP and renders the protein a dominant suppressor of protein trafficking between the ER and Golgi compartments (58,91).…”
Section: Retention Of C99 In the Er Affects The Biogenesis Of Both A␤mentioning
confidence: 99%
“…These results are in agreement with the previous in vitro transport assays. These studies have shown that membrane transport between the ER and Golgi [32] and intra-Golgi transport [33] are inhibited with NEM.…”
Section: Reconstitution Of P62 Cleavage In Slo-permeabilized Cellsmentioning
confidence: 99%
“…Since Rab-GDI binds to and inactivates several di¡erent Rabs, it acts as a general regulator [31]. Rab-GDI has been reported to inhibit intracellular vesicle tra¤cking in several systems, for instance between the ER and Golgi [32], inter-cisternal Golgi transport [33], and basolateral transport of MDCK cells [34]. In our reconstituted system, the addition of 5 WM recombinant Rab-GDI with the cytosol to SLO-permeabilized cells caused 50% reduction in the cleavage of p62 (Fig.…”
Section: Reconstitution Of P62 Cleavage In Slo-permeabilized Cellsmentioning
confidence: 99%